Influence of Gender on Total Serum Creatine Kinase and Creatine Kinase-Mb Levels of Nigerian Hypertensives - Efobi, Henry Afamuefuna; Bassey, Iya Eze (Birat Journal of Health Sciences, 2021)
Introduction: Hypertension is a long-term medical condition which when not detected and managed properly and on time often results to complications leading to disabilities and mortality. Gender has been known to affect the interpretation of some variables necessitating the need for gender-specific ranges.Objectives:This study evaluated total creatine kinase (CK) and creatine kinase-MB (CK-MB) isoenzyme activities of hypertensive subjects in Calabar, Nigeria and to assess if gender has influence on the activities of these enzymes.Methodology:One hundred and two participants were consecutively enrolled in this case control study. Serum total serum CK and CK-MB activity were evaluated in fifty one hypertensive and 51 normotensive subjects. The total CK levels were assessed using a spectrophotometric method while immunoinhibition method was used to determine the activity of CK-MB. Data was analyzed using Student’s t-test and Pearson’s correlation. Statistical significance was set at p0.05). There was also no significant correlation (p>0.05) between blood pressure, body mass index and the levels of CK and CK-MB.Conclusion:CK-MB activities were significantly higher in hypertensive subjects compared to normotensive controls. There were no gender specific differences in the CK-MB levels of male and female hypertensives. This cardiac marker should be included in the routine assessment of hypertensives and gender-specific considerations may not be necessary in the interpretation of the data.